Economic Evaluation of the HOPE Demonstration Field Experiment. Issue 4 (18th December 2018) - Cowell, Alexander J.; Barnosky, Alan; Lattimore, Pamela K.; Cartwright, Joel K.; DeMichele, Matthew
Abstract : Research Summary: In the program implemented in the Honest Opportunity Probation with Enforcement Demonstration Field Experiment (HOPE DFE), the following approach is taken: close monitoring; frequent drug testing; readily available substance abuse treatment; and swift, certain, and fair sanctioning to deter probationers from violating supervision conditions. We assessed in this study the costs and outcomes of the demonstration program across four jurisdictions, using 24 months of data from 625 probationers randomly assigned to probation as usual (PAU) or HOPE DFE. Our results reveal that the HOPE DFE group incurred more criminal justice costs than the PAU group over the observation period. Policy Implications: Our study results further demonstrate that HOPE in the DFE is associated with higher rates of incarceration and residential treatment, leading to an increase in total costs when compared with PAU. Jurisdictions choosing to implement programs like HOPE to hold probationers accountable would need additional resources from the criminal justice system to support the program.